Pelatihan Penerapan Pembelajaran Matematika Realistik (PMR) di SDN 03 Desa Cimaung Kecamatan Cikeusal Kabupaten Serang - Usep Sholahudin (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2017)
Realistic Mathematics Education (RME) is the utilization of reality, environment and event experienced by students and that will affect the level of students' understanding of learning materials and produce high achievement. The purpose of this Program Pengabdian kepada Masyarakat (PPM) is to conduct RME implementation training for teachers of SDN 03 Desa Cimaung and provide assistance for mastery of RME application in the classroom. The activities were conducted in two meetings. The first meeting discussed the RME approach to the classroom teaching process, objectives, characteristics and steps of RME. The second meeting was the assistance of the application of RME materials in the classroom. The methods used in carrying out this devotional activity are lecture, question and answer method, discussion, and demonstration. The result of this devotional activity is the increasing knowledge and insight of teachers at SDN 03 Desa Cimaung and applying the results of RME training in each class. Keywords: application, realistic mathematics education, knowledge